Heteropoly acid supported on titania as solid acid catalyst in alkylation of p-cresol with tert-butanol - Kumbar, Suresh M.; Shanbhag, G. V.; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
Butylation of p-cresol with tert-butanol was investigated on titania modified with 12-tungstophosphoric acid (TPA/TiO2) catalyst under vapor phase conditions. Catalysts with different TPA loadings (10-25 wt.%) and calcination temperatures (650-750 degrees C) were prepared by suspending titanium hydroxide in methanol solution of TPA followed by drying and calcination. These catalysts were characterized by surface area, XRD, P-31 MAS NMR, XPS, NH3-TPD, and FTIR pyridine adsorption. XRD results indicated that the presence of TPA retarded the crystallization of titania and stabilized TiO2 in anatase phase. P-31 MAS NMR indicated the presence of TPA in various forms (dispersed, highly fragmented and Keggin intact). These catalysts showed both Bronsted and Lewis acidity, and 20% TPA on TiO2 calcined at 700 degrees C (from here after words 20% TT 700) had the highest Bronsted as well as total acidity. Further, the catalytic activities were examined in tert-butylation of p-cresol with tent-butanol. The catalytic activity depended on TPA coverage, and the highest activity corresponded to the monolayer of TPA on titania. The most active catalyst 20% TT-700 gave 82% conversion of p-cresol and 89.5% selectivity towards 2-tert-butyl cresol (TBC), 2,6-di-tert-butyl cresol (DTBC) 7.5% and cresol-tert-butyl ether (CTBE) 3% under optimized conditions. The activity was always higher than that of WO3/ZrO2, sulfated zirconia (SZ), USY, H-beta zeolites and montmorillonite K-10 (K-10mont) under similar conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 2; 2-tert-butyl-p-cresol; 6-di-tert-butyl-p-cresol; Alkylation; heteropoly acid; p-Cresol; tert-butanol; titania

Tungstophosphoric acid supported on titania: a solid acid catalyst in benzylation of phenol with benzylalcohol - Kumbar, Suresh M.; Halligudi, Shivaraj B. (Catalysis Communictions, 2007)
{Benzylation of phenol with benzylalcohol was carried out in liquid phase over tungstophosphoric acid (TPA) supported on titania. The catalysts were prepared with different TPA (10-25%) loading by wet impregnation method, were calcined at 700 degrees C and characterized by XRD, surface area, FTIR and acidity of the catalysts was measured by temperature programmed desorption of NH(3)-TPD, FTIR pyridine adsorption. The catalysts have been represented by a general formula as xPTiO(2)-Y (where x = wt%
Keywords: benzyl ether; benzyl phenol; benzylalcohol; Heteropolyacid; phenyl benzyl ether; titania; tungstophosphoric acid